A Randomized Case-Series Study Comparing the Stability of Implant with Two Different Surfaces Placed in Fresh Extraction Sockets and Immediately Loaded. (3rd March 2016) - Vanden Bogaerde, Leonardo; Sennerby, Lars
Abstract : Background . Hydrophilic and moderately rough implant surfaces have been proposed to enhance the osseointegration response. Aim . The aim of this study was to compare early changes of stability for two implants with identical macrodesign but with different surface topographies. Materials and Methods . In 11 patients, a total of 22 implants (11 bimodal (minimally rough, control) and 11 proactive (moderately rough and hydrophilic, test), Neoss Ltd., Harrogate, UK) were immediately placed into fresh extraction sockets and immediately loaded. The peak insertion torque (IT) was measured in Ncm at placement. Resonance Frequency Analysis (RFA) measurements were made at baseline and 2, 4, 6, and 12 weeks after surgery. Results . The two implant types showed similar IT and RFA values at placement (NS). A dip of RFA values after 2 weeks followed by an increase was observed, where the test implant showed a less pronounced decrease and a more rapid recovery than the control implant. The test implants were significantly more stable than the control ones after 12 weeks. Conclusions . The results from the present study indicated that the hydrophilic and rougher test implant was more resistant to immediate loading and showed a significantly higher stability than the smoother control implant after 12 weeks.